Functional potential of coral assemblages along a typical Eastern Tropical Pacific reef tract. (December 2020) - Cabral-Tena, Rafael A.; López-Pérez, Andrés; Alvarez-Filip, Lorenzo; González-Barrios, F. Javier; Calderon-Aguilera, Luis E.; Aparicio-Cid, Cuauhtémoc
Highlights: Calcification, complexity, and the Reef Functional Index (RFI) were estimated. RFI was close to its maximum potential (96%) when pocilloporid abundance was ≥60% Reef functioning in the Mexican Pacific is mostly supported by pocilloporids. RFI decreased as the relative abundance of massive corals increased. Pocillopora damicornis is the primary reef builder in the southern Mexican Pacific. Abstract: Coral reefs are considered to be valuable ecosystems due to the goods and services that they provide. However, these ecosystem services are highly dependent on the physical structure of the reef, which in turn depends on the species composition of hermatypic corals. In this study, we explored the functional potential of reefs with a new index that takes into account coral cover, the calcification rate, rugosity, and the height of each species. In June 2019, we surveyed 11 reefs from the southern Mexican Pacific (15°40′N, 96°29′W−15°45′N, 96°5′W) to estimate coral cover and collect quantitative morphometric data of 15 haphazardly selected coral colonies per site (N = 102). We estimated the calcification rates and structural complexity of the species present and then calculated the Reef Functional Index (RFI), which estimates the species-specific functional contribution of the corals in reef systems by integrating their capacity to create complex three-dimensional structures through calcium carbonate precipitation with morphological complexity. We modelled the effects of shifting species compositions through a permutation approach with 6435 possible combinations. We found a mean coral cover of 48.5 ± 18.09% (±SD) dominated by Pocillopora damicornis, Pocillopora verrucosa, and Pocillopora capitata and low abundance of Porites panamensis and Pavona gigantea . The mean RFI was 0.71 ± 0.1. The permutation model showed that the RFI was very close to its maximum potential (96%) when the relative abundance of pocilloporids was ≥60% and decreased as the relative abundance of massive corals increased. At maximum evenness, the RFI value was at 92% of its maximum potential. Our data highlight the importance of pocilloporids to the functioning of reefs in the Eastern Tropical Pacific (ETP) and confirm that P. damicornis is the primary reef builder in the region. Nevertheless, our findings also highlight the vulnerability of these reefs given that branching corals are more susceptible to environmental disturbance than slow-growing massive corals. In a rapidly changing environment, the future of ETP reefs depends not only on the survival of pocilloporids but also on the ability of coral reefs to withstand highly variable oceanographic conditions as complete ecosystems.